Current Trends on Modes of Liability for Genocide, Crimes against Humanity and War Crimes (2010)
Today, there is not much dispute over the fact that genocide, crimes against humanity and war crimes are a manifestation of the phenomenon of macro-crime. This marks an important difference between international criminal law and national criminal law, which for the most part, focuses on individual crime. As a result, a proper understanding of the political, socio-economic and cultural context, as well as of criminal patterns, becomes of paramount importance for international criminal law. The specific features of macro-crime have led international criminal law to be particu larly concerned with the individual criminal responsibility of those senior superiors (top or high level perpetrators) who mastermind and direct the commission of large scale and or systematic criminal campaigns. The individual criminal responsibility of middle and low level perpetrators for their participation in the commission of some of the individual crimes that form part of such campaigns is increasingly a matter for national criminal law and domestic jurisdictions. As a result, the rules of attribution of criminal liability to senior superiors (also known as 'modes of liability) for their role in overall campaigns of genocide, crimes against humanity and war crimes nowadays constitute one of the core areas of international criminal law.